Self-Crypsis in Hakea Trifurcata as an Avian Granivore Deterrent - Groom, Philip; Lamont, Byron; Duff, H. (1994)
1. Hakea trifurcata is a dimorphic species that produces two distinct leaf types (broad and needle) with the broad leaves superficially resembling the fruits (follicles) that remain green at maturity. Feeding trials conducted with the white-tailed black cockatoo (Calyptorhynchus funereus latirostris), the major granivore of H. trifurcata, showed that the cockatoos removed fewer follicles when broad leaves were present than when they were absent. 2. Broad leaves are only produced by mature plants and the follicles are physically located near them. Follicles are difficult to distinguish among the broad leaves and apparently both represent similar search images to the cockatoos. This is therefore an unusual case of 'self-crypsis' with the follicles mimicking the unrewarding broad leaves. 3. The number of follicles that can be detected by the cockatoos is further reduced by broad leaves shielding the follicles. The increasing size of broad leaves the further away from follicles, together with the spatial distribution of broad leaves, may also aid in diverting the cockatoos from the nutritious follicles.